Effectiveness of Mensiang Plants (Actinoscirpus grossus) in Absorbing Linear Alkylbenzene Sulfonates (LAS), Copper (Cu), Nitrate and Phosphate - Astasagita, Sacinta Julia Astasagita; Rifiah, Amelia Cahya Putri; Prahardika, Bayu Agung; Irawanto, Rony (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Water is essential for all living creatures, but population growth is decreasing its availability. This is due to increased pollution from human activities, including domestic waste (like detergents), industrial waste (such as copper), and agricultural runoff (nitrates and phosphates). Various ways can be done to overcome water pollution, including phytoremediation techniques. One of the aquatic plants that has the potential as a phytoremediation agent is the Actinoscirpus grossus plants. This study aims to assess the ability of Actinoscirpus grossus plants to absorb LAS, Cu metal, nitrate and phosphate with several variations in concentration and determine the response of exposure to LAS, Cu metal, nitrate and phosphate to the growth of Actinoscirpus grossus plants. The method used is an experimental method using a completely randomized design (RAL) with 12 treatments and 3 replications (plant control; LAS 80 mg/L without plants; Cu 5 mg/L without plants; LAS 80 mg/L; Cu 5 mg/L; LAS 80 mg/L + Cu 5 mg/L) and (plant control; nitrate 30 mg/L without plants; phosphate 30 mg/L without plants; nitrate 30 mg/L; phosphate 5 mg/L; and nitrate 30 mg/L + phosphate 5 mg/L) with a detention time of 15 days. The results showed that mensiang plants proved effective in absorbing LAS and Cu contaminants as evidenced by the value of LAS removal power decreased by 74.52% in treatment LAS 80 mg/L + Cu 5 mg/L and Cu metal decreased by 83.40% in treatment Cu 5 mg/L. The effectiveness value of absorption by mensiang plants is most optimal in treatment Cu 5 mg/L which is 62.2%. Meanwhile, the results of the plant's absorption of nitrate 50-92% and 58-84% of nitrate in the combined contamination treatment. Phosphate was able to reduce up to 71-81% and 4-41% of phosphate in the combined contamination treatment. Actinoscirpus grossus plant weight was not significantly affected by nitrate and phosphate contamination. However, Actinoscirpus grossus experienced slight changes in leaf color due to nitrate and phosphate, these changes include leaves turning dark green in phosphate contamination, yellowish green in combination contamination and brown spots in some treatments.